Legal Analysis of the Implementation of Employment Agreements for Laborers or Workers in the Industrial Sector - Ihsan Ramadhan, Muhammad; Hasbi, Hasnan; Handayani, Dwi (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine the implementation of work agreements and the factors that influence the implementation of agreements for laborers or industrial workers in Soppeng Regency. This research uses empirical juridical legal research methods, focusing on qualitative analysis of primary data obtained from interviews, questionnaires and secondary data obtained from literature studies written in a descriptive report. The results of the research, the implementation of the work agreement is not well implemented because there are findings that are contrary to the applicable regulations and work agreements. The legal protection of industrial sector workers is less well protected due to violations of the work agreement that are less protected. There is a need for more intensive training and education programs to improve workers' understanding of their normative rights as stipulated in the labor law, as well as the contents of the work agreements they enter into. Also the establishment of a supervisory body from each industry to oversee the protection of labor agreements that can also increase worker productivity.